The Deserted Village, a Poem - Goldsmith, Oliver (The English Replicas. Oliver Goldsmith. The Deserted Village, 1770)
Presents a poem by Oliver Goldsmith published in 1770. Considered one of his major poems, it condemns rural depopulation and the pursuit of wealth